EGFR Somatic Mutations in Lung Tumors: Radon Exposure and Passive-smoking in Former- and Never-smoking U.S. Women - Taga, Masataka (2012)
BACKGROUND: Lung cancer patients with mutations in EGFR tyrosine kinase have improved prognosis when treated with EGFR inhibitors. We hypothesized that EGFR mutations may be related to residential radon or passive tobacco smoke. METHODS: This hypothesis was investigated by analyzing EGFR mutations in seventy lung tumors from a population of never and long-term former female smokers from Missouri with detailed exposure assessments. The relationship with passive-smoking was also examined in never-smoking female lung cancer cases from the Mayo clinic. RESULTS: Overall, the frequency of EGFR mutation was 41% [95% Confidence Interval (CI): 32-49%]. Neither radon nor passive-smoking exposure was consistently associated with EGFR mutations in lung tumors. CONCLUSIONS: The results suggest that EGFR mutations are common in female, never-smoking, lung cancer cases from the U.S, and EGFR mutations are unlikely due to exposure to radon or passive-smoking.